How Do Morphological Factors Influence the Green Nut Yield of Chinese Torreya? - Xi Chen; Shangbin Bai; Dongming Fang (Horticulturae, 2023)
As an important economic tree species, Chinese Torreya (Torreya grandis cv Merrillii) has been widely planted in the subtropical regions of China. However, it remains to be studied whether morphological traits are the key factors reflecting or affecting the green nut yield of Chinese Torreya, which is necessary for breeding research and plantation management. Therefore, in Zhuji in the Zhejiang Province, the central production area of Chinese Torreya, we investigated the morphological traits (height, ground diameter, under-crown height, crown width, and branching amount) and green nut yield of 120 randomly selected Chinese Torreya. Our results indicated that the differences in the morphological traits among Chinese Torreya individuals were relatively small, but those in the green nut yield traits were great. There was highly significant (p < 0.01) correlation between green nut yield and crown area and between green nut yield and root collar diameter (ground diameter). A moderate relationship (r = 0.38; p < 0.05) was observed between green nut yield and crown area, while a weak relationship (r = 0.294; p < 0.05) was detected between green nut yield and ground diameter. Tree height and branching amount had positive effects on green nut yield through other morphological traits, and under-crown height had indirect negative effects on green nut yield. Linear regression analysis showed a significant linear positive correlation between green nut yield and crown area, ground diameter, and crown width in the north–south and east–west directions (p < 0.01). These findings imply that if the tree height is fixed, increasing the ground diameter and crown area, appropriately increasing the branching amount, and reducing the under-crown height could be potential technical measures to improve the green nut yield of Chinese Torreya. Our study provides background information on green nut yield and its morphological traits in Chinese Torreya.